2021
DOI: 10.3390/plants10040715
|View full text |Cite
|
Sign up to set email alerts
|

WUSCHEL Overexpression Promotes Callogenesis and Somatic Embryogenesis in Medicago truncatula Gaertn

Abstract: The induction of plant somatic embryogenesis is often a limiting step for plant multiplication and genetic manipulation in numerous crops. It depends on multiple signaling developmental processes involving phytohormones and the induction of specific genes. The WUSCHEL gene (WUS) is required for the production of plant embryogenic stem cells. To explore a different approach to induce somatic embryogenesis, we have investigated the effect of the heterologous ArabidopsisWUS gene overexpression under the control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 57 publications
1
14
0
1
Order By: Relevance
“…In other studies, LEC1 has been described as a central regulator, controlling different parts of embryo morphogenesis and photosynthesis as well as seed development [ 41 ]. WUS is a morphogenic regulator that has been shown to induce or stimulate cellular differentiation in a range of species, such as Arabidopsis [ 16 ], Zea mays [ 34 ], and Medicago [ 42 ]. In cotton, the WUS gene had little to no expression in either genotype and developmental stage, suggesting that other genes have a more primary role in stimulating the transition from NEC to EC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, LEC1 has been described as a central regulator, controlling different parts of embryo morphogenesis and photosynthesis as well as seed development [ 41 ]. WUS is a morphogenic regulator that has been shown to induce or stimulate cellular differentiation in a range of species, such as Arabidopsis [ 16 ], Zea mays [ 34 ], and Medicago [ 42 ]. In cotton, the WUS gene had little to no expression in either genotype and developmental stage, suggesting that other genes have a more primary role in stimulating the transition from NEC to EC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used L er as a model genotype for SE recalcitrance and sought for ways to overcome this block. Previous studies had shown that expression of the transcription factor WUS enhances SE formation in several species (Arroyo‐Herrera et al ., 2008; Bouchabké‐Coussa et al ., 2013; Xiao et al ., 2018; Kadri et al ., 2021; Lou et al ., 2022). In the shoot meristem, WUS acts with miR394 to maintain stem cells in a yet unknown complex genetic and ecotype‐dependent manner (Knauer et al ., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factors from the WOX family regulate cell proliferation and differentiation, and different WOX genes have been found to stimulate regeneration processes. For example, WUS or its orthologs have been shown to induce regeneration in many plant species and can be applied as morphogenic regulators to speed up the transformation process or to make it possible [ 22 , 23 ]. WOX2 and 8 induce regeneration in tobacco [ 24 ], and MtWOX9-1 has been shown to stimulate SE in M. truncatula [ 15 ].…”
Section: Discussionmentioning
confidence: 99%